Advanced Fatigue Damage Analysis of Adhesive Bonded Joints - Xu, Xintian (Cranfield University, 2025)
This thesis presents an investigation of advanced fatigue damage analysis in adhesively bonded structures through proposing a novel local-strain-based method for predicting crack propagation and damage evolution. Unlike the common cohesive model-based method for calculating damage increments according to Paris law, the proposed local-strain-based method focuses on defining damage by analysing the strain field in the local fracture process zone (FPZ). This approach challenges traditional research methods that rely on Paris law, like those commonly used in the study of metal fatigue cracks. The thesis provides evidence of the superiority of the proposed method under certain conditions and demonstrates the feasibility of this research method. This study utilized a complementary approach, combining numerical simulation analysis and experimental work. The first stage of the research focused on proposing a novel method that differs from the traditional approach based on Paris Law. The emphasis was placed on introducing a new method that differs significantly in terms of fracture mechanisms from conventional approaches. Two double cantilever beams (DCB) models with different adherend thickness (1.6 mm &12.7 mm) were employed for finite element (FE) simulation. The local-strain-based damage model was implemented using the VUMAT subroutine in the commercial finite element analysis (FEA) software ABAQUS. Material parameters for the damage model were calibrated using published test data and were subsequently used to predict specimens of varying geometric sizes. Results demonstrated that the local-strain-based damage model can effectively reproduce the relationship between crack growth rate (da/dN) and Gmax observed in the test data. Moreover, two commonly recognized methods based on cohesive damage models were selected for make a benchmark study with the local-strain-based method. The two methods defined the damage rate based on the global Gmax and were implemented using two VUMAT subroutines in ABAQUS. By comparing the simulation results predicted by the three models with the experimental data, the local-strain-based method exhibited 15% increase of geometry-independence and comparable reducing ability to the test results. During the second stage, three aluminium DCB joints with varying adherend thickness (5mm, 8mm, and 15mm) were manufactured using a toughened epoxy-based adhesive, 3M2216, and subjected to Mode I quasi-static and fatigue tests. Quasi-static tests, conducted in accordance with the standard ASTM 5528, were used to determine the critical toughness of each DCB joint. The fatigue tests were initiated at the same critical toughness level to investigate the impact of adherend thickness on the results. Full-field speckle images and local speckle images taken by a high-definition camera were used in combination with digital image correlation (DIC) technology to extract the crack length, rotation angles of the crack tip, and local strain field map around the crack tip. The local strain field maps for specimens with different thicknesses were used to identify the FPZ and to reveal damage evolution within the FPZ. Observations of the FPZ in specimens with different adherend thicknesses at the same J-value revealed that the FPZ area increases with increasing specimen thickness, reflecting the overall dynamic movement of damage transmission within the FPZ. Differences in FPZ area and internal damage evolution both contribute to differences in crack propagation rates. Based on the results, the third stage of this research focused on verifying and calibrating the proposed damage model. Additional simulation was conducted to determine the model's ability to accurately predict crack growth and damage evolution within the failure process zone, and to compare these predictions with experimental results. Notably, the local-strain-based method exhibited superior predictive accuracy in modelling type I fatigue crack growth for various geometric sizes, as compared to the traditional approach based on Paris Law. These findings have significant implications for the design of adhesive structures. Overall, this research provides compelling evidence that the proposed novel damage model is both efficient and accurate, offering a better explanation of the fracture mechanism of fatigue crack growth in adhesively bonded joints.
Keywords: Adhesively Bonded Joints; Fatigue Crack Growth; Cohesive Zone Methods; Fracture Process Zone; Paris Law; Fracture mechanics; Simulation